The production of social space in Lefebvre: a “socionatural” critique - Garcia Simões, Roberto (Geografares, 2025)
Based on the works of the French thinker Henri Lefebvre, especially "La producción del espacio", it is identified that, in his attempt to elaborate a unitary theory of space, "ecology" and "environment" are refuted. Dominating these works are the division between nature and society, the bipartition of nature, the primal view of nature as "raw material," the social-human collage, and a single urban world. In an anthropocentric vision, the hegemonic option is for the "development of productive forces" as a path to "another mode of production," while simultaneously acknowledging the subordinate nature of "risks," "threats," and even the "destruction of man." Faced with these conceptions, another possibility is to revisit the Earth within a world of worlds.
Keywords: Henri Lefebvre; production of space; nature